Evaluation of Seismic Protection Methods for Buried Fuel Pipelines Subjected to Fault Rupture - Gantes, Charis J.; Melissianos, Vasileios E. (Frontiers in Built Environment, 2016)
Buried steel fuel pipelines are critical lifelines for the society and the economy, but are very vulnerable to earthquake-induced ground failure. Traversing seismic areas inevitably results to several pipe – fault crossings. Fault rupture forces a buried pipeline to undergo deformations that could be substantial and heavily endanger its integrity. Due to the grave consequences of a potential pipe failure, mitigating measures are commonly applied at pipe – fault crossings to reduce the effects of a potential fault activation. In this paper, a comparative review of several measures that are used in practice or have been proposed in the technical literature is presented. Numerical analyses are then carried out to compare the effectiveness of commonly used measures and to extract conclusions regarding their applicability. Results indicate that the most efficient among the evaluated measures are pipe placement within culverts and use of flexible joints. Trench backfilling with pumice is a moderately effective measure in terms of pipe protection, while steel grade upgrade, wall thickness increase and pipe wrapping with geotextile are found to be insufficient protection methods.